2022
DOI: 10.1038/s41598-022-11083-1
|View full text |Cite
|
Sign up to set email alerts
|

Autistic-like behavioral effects of prenatal stress in juvenile Fmr1 mice: the relevance of sex differences and gene–environment interactions

Abstract: Fragile X Syndrome (FXS) is the most common heritable form of mental retardation and monogenic cause of autism spectrum disorder (ASD). FXS is due to a mutation in the X-linked FMR1 gene and is characterized by motor, cognitive and social alterations, mostly overlapping with ASD behavioral phenotypes. The severity of these symptoms and their timing may be exacerbated and/or advanced by environmental adversity interacting with the genetic mutation. We therefore tested the effects of the prenatal exposure to unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 67 publications
7
41
1
Order By: Relevance
“…Interestingly, we proved that the duplication of chromosome 6 is paternally inherited. The presence of the same alteration in the father, which did not show any apparent functional defect until his precocious death (from myocardial infarction), suggests an influence of additional genetic and/or environmental causes for the proband, consistent with the evidence of “multiple genetic hits” and the occurrence of complex genetic, hormonal and environmental interactions in the emergence of neuropsychiatric disorders [ 72 76 , 82 ]. In this regard, the exome analysis of the patient indicated the presence of seven known potential pathogenic variants in SLC6A19 , PRKCQ , UCP3 , ERCC4 , TYR , SLC12A3 and SERPINA7 genes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Interestingly, we proved that the duplication of chromosome 6 is paternally inherited. The presence of the same alteration in the father, which did not show any apparent functional defect until his precocious death (from myocardial infarction), suggests an influence of additional genetic and/or environmental causes for the proband, consistent with the evidence of “multiple genetic hits” and the occurrence of complex genetic, hormonal and environmental interactions in the emergence of neuropsychiatric disorders [ 72 76 , 82 ]. In this regard, the exome analysis of the patient indicated the presence of seven known potential pathogenic variants in SLC6A19 , PRKCQ , UCP3 , ERCC4 , TYR , SLC12A3 and SERPINA7 genes.…”
Section: Discussionmentioning
confidence: 65%
“…We hypothesize that gender differences and specificity could have a key role in explaining the absence of broader behavioral psychiatric-like alterations in Ddo -overexpressing mice. Indeed, it is well known that while some behavioral deficits described in certain neurodevelopmental disorders are predominantly male‐specific, there are also female‐specific changes that might depend on a complex interaction between genes, sex hormones and environmental factors [ 72 76 ]. Therefore, we cannot exclude that the DDO gene duplication and the consequent metabolic D-aspartate dysfunction might produce behavioral alterations that depend on the gender, as well as on the age, strain and/or behavioral task used.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, testing Fmr1-KO mice from adulthood onward has still a translational value in itself, since the pathological phenotypes of FXS and ASD are persistent in older patients. Here, our main aim was to evaluate whether the effects of prenatal stress we observed before in juvenile mutants in our previous study on an independent cohort of mice (Petroni et al, 2022) could be confirmed later on, i.e., in adult and old animals. Interestingly, we could detect the same effect observed in juveniles on the Y maze performance, while several stress effects we found here were absent in juveniles, thus underlining the importance of behavioral testing of Fmr1-KO mice at multiple ages for the study of gene-environment interactions.…”
Section: Discussionmentioning
confidence: 94%
“…While the exposure to environmental stimulation is able to attenuate/delay the appearance of behavioral alterations both in FXS patients and Fmr1-KO mice ( Dawson et al, 2002 ; Oddi et al, 2015 ), the opposite effects have been described following stressful experiences. The chronic exposure to aversive and stressful events, especially during early life phases, is indeed known to exacerbate the behavioral symptoms of FXS patients ( Hessl et al, 2001 ; Dyer-Friedman et al, 2002 ) and to anticipate the appearance of certain behavioral deficits in Fmr1-KO mice ( Petroni et al, 2022 ). More in general, a large body of human research suggests that the offspring of mothers who experienced high levels of stress during pregnancy are more likely to have problems in their neurobehavioral development (reviewed in Van den Bergh et al, 2005 ; Rice et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…FXS is characterized by motor, cognitive, and social alterations, mostly overlapping with ASD behavioral phenotypes. The severity of these symptoms and their timing may be exacerbated or advanced by environmental adversity interacting with the genetic mutation [ 81 ]. Symptoms of ASD are frequently observed in patients with FXS; however, behavioral similarities and differences between FXS and ASD are important in the causes and correlations of ASD with FXS.…”
Section: Dysregulation Of the Ecs In Fragile X Syndromementioning
confidence: 99%